Spatial temporal changes in water quality of an urban / sub-urban / rural watershed influenced by land use - Prado Velasco, Pablo Edmundo ; 0000-0002-8051-0195; Oporto, Carla Gabriela; Jönsson, Karin; Rejas, Danny; Martinez, Virgilio ; 0009-0000-4268-7347; Marañon, Martin; Persson, Kenneth M (9th IWA-ASPIRE Conference & Exhibition. One Water for Smart Cities, Kaohsiung, Taiwan, 2023-10-22 - 2023-10-26, 2023)
Geographic information systems are used to integrate historical water quality data with information layers derived from diverse sources and represents important tools for the water resources management at watershed scale. This study aimed to collect data sources at the watershed level and compare coincident water quality parameters to find spatial and temporal changes related to land use / land cover in a priority watershed of the Bolivian central Andes. Historical data of water quality public repository of the Cochabamba Water Management was reviewed and selected for the study area. Coincident variables (pH, electrical conductivity, turbidity, dissolved oxygen, calcium, chlorides, sulphates and nitrates) and types of water quality (D=Poor to A=Very good) were compared to percentages of land cover / land use calculated based on World land cover layer 2021. The Chocaya River has low temporal variability of good water quality in the upper part of the river, but lower water quality in the lowest part. Spatial variability of water quality is related to land cover / land use, with a majority of grassland (66 to 80%), shrubland (9 to 17%), tree cover (5 to 14%), and bare / sparce vegetation (4 to 16%) in the upper part of the river, while the lower part reports a decrease in water quality due to land cover / land use variations of croplands (14 to 21%) and built-up areas (21 to 63%), showing a clear impact of urban activities. The use of GIS helps to display variation in water quality and to communicate results with stakeholders. Future studies should consider collecting data in both seasons and with more variables to understand watershed dynamics and analyse spatial or multivariate statistics for an integrated water quality management to prevent natural disasters and ecosystem service degradation.
Keywords: Land cover / Land use change; water quality; spatial temporal changes; GIS